Meningkatkan Kreativitas dan Keterampilan Hidup Melalui Model Project Based Learning pada Pembelajaran Senam Lantai. - kahri, Ma'ruful Kahri (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2025)
This study began with an analysis of the results and evaluation of gymnastics learning in the Physical Education study program. Lecturers had difficulty analyzing the impact of gymnastics learning on students' life skills and creativity because they had been using instruction-based learning that emphasized technique and knowledge alone, which tended to make students passive, thereby inhibiting the development of creativity and life skills values. The purpose of this study was to determine the effect of the PjBL model on students' creativity and life skills and to determine the extent of improvement in creativity and life skills through the PjBL model. The research method used a quasi-experiment with a descriptive quantitative approach. The research design was a pretest-posttest control group design. The population consisted of all JPOK FKIP ULM students. Sampling used purposive sampling. The sample consisted of 80 students who took the basic gymnastics learning course. Sampling was done using purposive sampling. The research instruments used were the LSSS questionnaire for life skills and the TTCT for creativity. The results showed a significant effect of the PjBL learning model on life skills (P = 0.00 < 0.05) and creativity (P = 0.03 < 0.05). The PjBL learning model can improve students' life skills, with the problem-solving and decision-making component increasing the most (80.51%), followed by the creativity component, namely flexible thinking, which increased by 77.25%. These results will serve as a reference for future learning to use a student-centered learning model so that floor gymnastics learning becomes more meaningfu